ADAPTIVE BLOCKCHAIN FRAMEWORK FOR TRANSACTION VALIDATION AND DATA ASSURANCE (International Journal of Food and Nutritional Sciences, 2022)
ABSTRACT:Trust needs to be established before data transfer becomes commonplace. Data consumers worry about the information's accuracy, yet few data owners are willing to part with their data since they don't know how to gain others' trust. By facilitating consensus on an immutable ledger, blockchain technology paves the way for transparent and decentralized governance. This endeavor strengthens data integrity by creating a blockchain-based end-to-end data trust architecture. In addition, we offer a dynamic method for choosing the optimal amount of transaction validators and calculating the trust value.